Effect of biological agents on synovial tissues from patients with rheumatoid arthritis. Issue 2 (3rd March 2020) - Kubota, Ayako; Suguro, Toru; Nakajima, Arata; Sonobe, Masato; Tsuchiya, Kazuaki
Abstract: Objectives: To compare the inflammation of synovium before and after biological agents in the patients with rheumatoid arthritis (RA) and to investigate the association between synovial histopathology and disease activity. Methods: Synovial tissues were obtained during operations from 34 patients before and after treatment with biological agents. The synovial tissue was evaluated using hematoxylin and eosin staining. Synovial histopathology was evaluated by Rooney score. Results: The Rooney score was also significantly decreased after treatment with biological agents in all items ( p  < .001). After the treatment with biological agents, Moderate disease activity group had significantly higher scores of focal aggregates of lymphocytes ( p  = .02), diffuse infiltrates of lymphocytes ( p  = .019), and the Rooney total scores ( p  = .002) than remission and low disease activity groups. Conclusion: Our results demonstrated that biological agents significantly decreased the RA synovial inflammation and synovial histopathology in sublining layer reflected disease activity.